TRENDS OF CONSUMER PURCHASES VIA SOCIAL MEDIA ACCORDING TO THE STIMULUS-ORGANISM-RESPONSE (SOR) MODEL - Vonoga, Aija (Journal of Regional Economic and Social Development, 2021)
The theme of this paper is ,,Trends of Consumer Purchases via Social Media according to the Stimulus-Organism-Response (SOR) Model’’. Social media are an important platform for entrepreneurship development, and a lot of entrepreneurs are using social media for marketing and selling activities in order to increase sales and attract potential customers. The topicality of the research is based on economic development requirements. The aim of the research – to identify the situation and to develop proposals for entrepreneurs and managers in Latvia. The tasks of the research are the following: to develop a survey, to carry out theoretical research; to develop proposals. The research period was from March until June 2021. General scientific research methods were used in the research: the monographic and descriptive methods, the survey method, the comparative analysis method for studying the concept of SOR at social networking and future development possibilities. The survey conducted in the study showed the tendencies of Latvian consumers' purchases via social media. The study hypothesis confirmed that according to the Stimulus-OrganismResponse Model, advertising, opinion leaders, and user-generated content act as the stimulus (S) to evoke positive emotions (O), which later leads to impulse purchases (R) for consumers.